Pengembangan Materi Ajar Kimia Larutan Penyangga yang Interaktif Untuk Siswa SMA - Putri Rosida; Mahmud Mahmud; Eddiyanto Eddiyanto (Jurnal Pendidikan Kimia (JPKim), 2015)
Abstract. This study aims to obtain web-based interactive chemicals teaching materials. Form of research is a descriptive study. This type of research, including research and development. Subject is basic teaching materials buffer solution. The sample used in this study consisted of 20 chemistry teachers in class XI in Medan, 2 chemistry lecturers, general chemistry lecturer and a media lecturer of Universitas Negeri Medan, and 80 students. The selection of the sample in the study using purposive sampling technique. The results of the analysis based on stadart content, competence and indicator obtained, feasibility aspects of the content of 4.42 is very valid, it means very feasible and does not need to be revised, the feasibility of presenting 4.13 is valid, it means feasible and does not need to be revised. Teaching materials that have been developed then tested to students. Testing of students using two classes, experimental and control classes. Towards the experimental class students are given a developed web-based interactive chemistry teaching materials, while the control class using teaching materials that it carries. Based on test results obtained improvement of learning outcomes (gain) experimental grade students (68.25%) is higher than the increase in learning outcomes (gain) control class (61.36%). Keyword: interactive chemistry teaching materials, web, research and development (R&D), buffer solution